Next generation designer virus-like particle vaccines for dengue - Rahul Shukla; Viswanathan Ramasamy; Ravi Kant Rajpoot; Upasana Arora; Ankur Poddar; Richa Ahuja; Hemalatha Beesetti; Sathyamangalam Swaminathan; Navin Khanna (Taylor & Francis Group, 2019)
Introduction: A safe and efficacious vaccine for dengue continues to be an unmet public health need. The recent licensing of a dengue vaccine (Dengvaxia) developed by Sanofi has brought to the fore the safety issue of vaccine-induced infection enhancement. Areas covered: This article focuses on two new yeast-produced tetravalent dengue envelope domain III-displaying virus-like particulate vaccine candidates reported in early 2018 and reviews the rationale underlying their design, and pre-clinical data which suggest that these may offer promising alternate options. Expert commentary: These are the only vaccine candidates so far to have demonstrated the induction of primarily serotype-specific neutralizing antibodies to all dengue virus serotypes in experimental animals. Interestingly, these antibodies lack infection-enhancing potential when evaluated using the AG129 mouse model.